2012
DOI: 10.1111/j.1365-2621.2012.03030.x
|View full text |Cite
|
Sign up to set email alerts
|

Gas‐producing and spoilage potential of Enterobacteriaceae and lactic acid bacteria isolated from chilled vacuum‐packaged beef

Abstract: Summary This study aimed to enumerate and identify lactic acid bacteria and Enterobacteriaceae from spoiled and nonspoiled chilled vacuum‐packaged beef and determine their potential to cause blown pack spoilage. These microbial groups were also enumerated in nonspoiled samples and detected in abattoir samples. The potential of isolates to cause ‘blown pack’ spoilage of vacuum‐packaged beef stored at chilled temperature (4 °C) and abuse temperature (15 °C) was investigated. Populations of lactic acid bacteria i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 12 publications
0
7
2
1
Order By: Relevance
“…16S rRNA gene amplicon sequence analysis also showed that both packages of pork had a substantial fraction of LAB including Lactobacillus, Carnobacterium and Lactococcus, which is in agreement with previous findings that LAB are often predominant on VP meats (Doulgeraki et al 2012;Youssef et al 2017). BPS caused by LAB has been reported for VP beef and lamb; however, different from the case in this study, this type of BPS normally occurs at the end of the storage life of VP meats and the package is usually less distended (Brightwell et al 2007;Chaves et al 2012). Enterobacteriaceae have also been associated with BPS at late stages of VP meat storage when they prevail among the microbiota (Brightwell et al 2007;Chaves et al 2012).…”
Section: Resultscontrasting
confidence: 75%
See 1 more Smart Citation
“…16S rRNA gene amplicon sequence analysis also showed that both packages of pork had a substantial fraction of LAB including Lactobacillus, Carnobacterium and Lactococcus, which is in agreement with previous findings that LAB are often predominant on VP meats (Doulgeraki et al 2012;Youssef et al 2017). BPS caused by LAB has been reported for VP beef and lamb; however, different from the case in this study, this type of BPS normally occurs at the end of the storage life of VP meats and the package is usually less distended (Brightwell et al 2007;Chaves et al 2012). Enterobacteriaceae have also been associated with BPS at late stages of VP meat storage when they prevail among the microbiota (Brightwell et al 2007;Chaves et al 2012).…”
Section: Resultscontrasting
confidence: 75%
“…BPS caused by LAB has been reported for VP beef and lamb; however, different from the case in this study, this type of BPS normally occurs at the end of the storage life of VP meats and the package is usually less distended (Brightwell et al 2007;Chaves et al 2012). Enterobacteriaceae have also been associated with BPS at late stages of VP meat storage when they prevail among the microbiota (Brightwell et al 2007;Chaves et al 2012). Both packages of pork examined in this study had only a small portion (<2%) of Enterobacteriaceae.…”
Section: Resultscontrasting
confidence: 74%
“…The psychrotrophic members of the Enterobacteriaceae family and Enterococcus are frequent members of the spoilage microflora of vacuum‐packed meats and lightly preserved fish products like cold‐smoked salmon or shrimps (Gram and others ; Daalgard and others ; Mejlholm and others ; Jaffrès and others ; Alfaro and Hernandez ; Säde and others ). In the meat sector, Enterobacteriaceae have also been described as being potential causative agents of the “blown pack” spoilage of meats, characterized by abundant production of gas, off‐odors, and exudates together with proteolysis and modifications of pH and color (Brightwell and others ; Adam and others ; Chaves and others ). Concerning Enterococcus sp., this genus is described as positively contributing to the pH decrease and to the modification of the texture and/or the sensorial characteristics of some fermented food.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the ability of psychrotrophic Clostridium isolated from Brazilian vacuumpackaged beef and the influence of the combination of shrinking temperature and vacuum pressure during packaging was studied. Besides, recent research conducted by Chaves, Silva, Sant'Ana, Campana, and Massaguer (2012) showed that others species such as H. alvei and Lactobacillus pentosus were also capable to promote the blown pack.…”
Section: Discussionmentioning
confidence: 97%